1965
DOI: 10.1128/jb.90.4.1036-1044.1965
|View full text |Cite
|
Sign up to set email alerts
|

Bacillary Necrosis, a Disease of Larval and Juvenile Bivalve Mollusks I. Etiology and Epizootiology

Abstract: Lethal bacterial infections of a variety of hatchery-spawned bivalve mollusk larvae and juveniles have been studied. The symptoms of the disease and the course of the infection are described. Four biotypes and five antigenic types of bacteria, pathogenic for the larvae of five species of bivalve mollusks, were isolated and described in some detail. All are gram-negative motile rods. Comparative studies were made of a fairly large number of similar bacteria isolated from presumably normal marine fauna. None of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
8

Year Published

1975
1975
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(80 citation statements)
references
References 7 publications
5
67
0
8
Order By: Relevance
“…After removing the unchallenged oysters from the experimental trays, we subjected the remaining eight oysters/family/tray to a bacterial challenge by turning off the incoming water flow and adding log‐phase V. tubiashii culture (ATCC 19106) (Tubiash et al. 1965; 1970) to the trays for 3 h in static water, after which we restored water flow and allowed the bacteria to flush gradually from the trays.…”
Section: Methodsmentioning
confidence: 99%
“…After removing the unchallenged oysters from the experimental trays, we subjected the remaining eight oysters/family/tray to a bacterial challenge by turning off the incoming water flow and adding log‐phase V. tubiashii culture (ATCC 19106) (Tubiash et al. 1965; 1970) to the trays for 3 h in static water, after which we restored water flow and allowed the bacteria to flush gradually from the trays.…”
Section: Methodsmentioning
confidence: 99%
“…Vibriosis is the main disease currently hindering the success of the hatchery culture of bivalves. Different species of Vibrio have been described as opportunistic pathogens associated with mortalities during larval development: V. alginolyticus , V. anguillarum , V. neptunius , V. pectenicida , V. splendidus and V. tubiashii (Tubiash, Chanley & Leifson ; Brown ; Jeffries ; Riquelme et al . , ; Nicolas et al .…”
Section: Introductionmentioning
confidence: 99%
“…No specific clinical symptoms such as adhesion of ciliates and velum necrosis on the dead larvae were observed microscopically (Figure a). Specific clinical signs of V. coralliilyticus, V. tubiashii and OVVD infection such as velum necrosis, velar degeneration with loss of cilia and velar epithelium (Elston & Wilkinson, ; Sugumar et al, ; Tubiash et al, ) (Figure b, unpublished data) were not observed. In addition, protozoans including parasitic organisms were also not observed except feeding phytoplankton.…”
Section: Resultsmentioning
confidence: 94%
“…During mass mortality of the bay scallop larvae in the southern regions of Korea, it was observed that 5–10‐day‐old larva sank to the bottom of the tank. Based on this observation, this study focused on OsHV‐1, OVVD, V. coralliilyticus and V. tubiashii infections which were have been reported to demonstrate similar symptoms (Elston & Wilkinson, ; Farley et al, ; Rodgers, Arzul, Carrasco, & Furones Nozal, ; Sugumar, Nakai, Hirata, Matsubara, & Muroga, ; Tubiash, Chanley, & Leifson, ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation